2016
DOI: 10.1016/j.cmi.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Equal sensitivity of the new generation QuantiFERON-TB Gold plus in direct comparison with the previous test version QuantiFERON-TB Gold IT

Abstract: QuantiFERON-TB Gold IT analyses interferon-γ release from CD4(+) T cells after stimulation with specific tuberculosis (TB) antigens. Its sensitivity is approximately 80% for active TB. A new test generation (QFTGplus) also analyses the response of CD8(+) T cells. We investigated both test generations in a direct head-to-head comparison in a German pulmonary hospital. Sensitivity rates for active TB were identical, no matter whether diagnosis was bacteriologically confirmed or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 10 publications
8
37
0
Order By: Relevance
“…QFT-Plus specificity among low-risk subjects in Europe was 97% (95%CI 92–99) 20. Similar results have been reported from Germany and Japan, where head-to-head comparisons of QFT-Plus and QGIT among predominantly immunocompetent patients showed similar test sensitivities 21,22…”
Section: Discussionsupporting
confidence: 78%
“…QFT-Plus specificity among low-risk subjects in Europe was 97% (95%CI 92–99) 20. Similar results have been reported from Germany and Japan, where head-to-head comparisons of QFT-Plus and QGIT among predominantly immunocompetent patients showed similar test sensitivities 21,22…”
Section: Discussionsupporting
confidence: 78%
“…The new CD8+ -specific peptides have been added to increase the sensitivity of the test because it has been shown that Mtb-specific CD8+ T-cells are mainly associated to active TB [44,45,46,47]. The first data on the performance of QuantiFERON TB Plus were reported recently [48,49,50]. When compared with the previous test version of QFT-GIT [50], equal sensitivity of the new generation QFT-plus was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The first data on the performance of QuantiFERON TB Plus were reported recently [48,49,50]. When compared with the previous test version of QFT-GIT [50], equal sensitivity of the new generation QFT-plus was observed. However, at the moment it is unknown the performance of the QFT-plus as a tool to monitor TB therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The test is interpreted as positive when either antigen tube result is positive. Published data on this newer assay are limited (29), but studies are ongoing. There is no policy guidance on QFT-Plus yet.…”
Section: Igrasmentioning
confidence: 99%